2002
DOI: 10.1089/089771502753754037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials in Head Injury

Abstract: Traumatic brain injury (TBI) remains a major public health problem globally. In the United States the incidence of closed head injuries admitted to hospitals is conservatively estimated to be 200 per 100,000 population, and the incidence of penetrating head injury is estimated to be 12 per 100,000, the highest of any developed country in the world. This yields an approximate number of 500,000 new cases each year, a sizeable proportion of which demonstrate signficant long-term disabilities. Unfortunately, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
548
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 815 publications
(559 citation statements)
references
References 42 publications
4
548
1
6
Order By: Relevance
“…It is estimated that the prevalence of Americans with chronic TBI‐related disability is 5.3 million 2, 3, 4, 5. The magnitude of this problem has led to extensive pre‐clinical research and clinical trials to improve functional outcomes 6. Despite success in animal models, all Phase III human clinical trials to date have failed 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that the prevalence of Americans with chronic TBI‐related disability is 5.3 million 2, 3, 4, 5. The magnitude of this problem has led to extensive pre‐clinical research and clinical trials to improve functional outcomes 6. Despite success in animal models, all Phase III human clinical trials to date have failed 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Despite success in animal models, all Phase III human clinical trials to date have failed 7, 8, 9, 10. Consensus conferences have concluded that biomarkers will be critical for the development of effective TBI therapies targeted at injury‐specific mechanisms 6, 11…”
Section: Introductionmentioning
confidence: 99%
“…In the field of traumatic brain injury (TBI), however, not a single multicenter phase III RCT on neuroprotective agents has convincingly shown benefit. [1][2][3] As a consequence, a sense of disappointment prevails; basic science researchers are increasingly frustrated that their hard and promising work performed under clean experimental conditions does not seem to transfer into the "dirty" clinical situation, and there is some reluctance by pharmaceutical companies to embark on a new high-cost venture in TBI. However, trials conducted so far have not definitively established the lack of possible benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The later description of the extended GOS (GOSE) 7 is in the top 25 cited papers on traumatic brain injury (TBI) 8 . The GOS in its original or extended form is recommended as the outcome measure to be used for major trauma and for head injury by, among others, the National Institute of Neurological Disorders and Stroke, the NIH National Institute of Child Health and Human Development TBI Clinical Trials Network and the Department of Health in England [9][10][11] . In the USA, the GOS is the core measure used for outcome research in TBI in the Common Data Elements project 12 .…”
mentioning
confidence: 99%